Tectonic implications of mantle source changes recorded by Eocene-Oligocene basalts from the Dillon volcanic field southwest Montana (USA) - Everhart, Wyatt Matthew (My University, 2025)
Basalts of the Eocene to Oligo-Miocene Dillon volcanic field Montana (U.S.A.) record the change from dominantly compression to extensional tectonics, within the northern Rocky Mountains and accordingly, also present across the North American Cordillera. The Dillon volcanic field is composed of lavas and intrusives that crop out across southwestern Montana, but most prominently in the Gravelly Range, where they define multiple eruptive centers (e.g., Black Butte, Lion Mountain, etc.). Prior work suggested lower Dillon volcanism-initiated ca. ~50-39 Ma, which occurred adjacent to coevally with the 51-40 Ma central Idaho Challis and the 54-44 Ma Absaroka volcanism. Multiple tectonic models have been proposed to explain the ~33-16 Ma middle and upper Dillon volcanism (e.g., Farallon slab rollback, slab tearing/foundering, lithospheric drip), which erupted during the later period of regional extension and basin sedimentation. Dillon volcanic rocks have mainly high-K compositions, are primarily subalkaline, but include eruptions of small volume alkali basalts. The lower Dillon rocks tend to range from basaltic trachyandesites to basaltic andesites. Middle/upper Dillon rocks include basanite, trachybasalt, basalt, basaltic andesites, and basaltic trachyandesites. Basalts of the Dillon volcanics are often olivine rich with groundmass of clinopyroxene and plagioclase; however, middle/upper samples tend to contain titanaugite, reflecting their alkali compositions. Lavas, especially dikes and sills in the Gravelly Range, often contain small ~1-2 cm-wide crustal xenoliths, such as Eocene Renova formation sediment. Dikes and sills cut Renova strata, and some Dillon lavas overlying Renova sediments. These xenoliths, along with microscopic quartz xenocrysts, are evidence of crustal interaction, though assimilation-fractional crystallization modelling shows that this interaction had a small effect on the basalt bulk rock chemistry and their Sr-Nd isotope-compositions. Trace element and Sr-Nd isotope ratios of the lower Dillon volcanics display arc-like signatures, which we suggest reflect subduction of the Farallon plate (e.g., Ta/Th <0.2, ⁸⁷Sr/⁸⁶Sri 0.7072 - 0.7078; ¹⁴³Nd/¹⁴⁴Ndi 0.51204 - 51229). Middle and upper Dillon rocks have intermediate Ta/Th (0.2-0.6) coupled with Sr-Nd isotopes (⁸⁷Sr/⁸⁶Sr 0.7059 - 0.7043; ¹⁴³Nd/¹⁴⁴Ndi 0.51204 - 0.51236) suggesting magma sources from metasomatized lithosphere mantle. Some middle/upper Dillon rocks have high Ta/Th (>0.6) with low ⁸⁷Sr/⁸⁶Sr (0.7043-0.7049) which might suggest an asthenosphere source, however, these rocks have lower, and thus more enriched, ¹⁴³Nd/¹⁴⁴Ndi (0.51203-0.51232), unlike any other documented regional Cenozoic volcanics and we suggest this likely reflects lower crustal interaction. We propose that the middle Dillon volcanics are sourced from metasomatized subduction-affected lithospheric mantle that melted after the initiation of slab tearing/rollback and upwelling asthenosphere. Eruptions of middle Dillon basalts occurred contemporaneously with the onset of regional extensional tectonics and Renova basinal strata deposition. Continued extension resulted in eruptions of the upper Dillon alkali basalts, which we show were sourced from asthenosphere that interacted with low crust (or possibly lithospheric mantle melts) and resulted in whole rock ⁸⁷Sr/⁸⁶Sri and ¹⁴³Nd/¹⁴⁴/Ndi ratios that resemble enriched mantle (e.g., EM1-like).
Keywords: Dillon volcanics, Dillon volcanic field DVF; Sr-Nd Isotopes; Asthenosphere and Lithosphere mantle; Whole rock geochemistry; Eocene-Oligo-Miocene; Petrogenesis